Burden of disease progression in patients with multiple myeloma in the US. Issue 1 (2nd January 2020) - Hagiwara, May; Panjabi, Sumeet; Delea, Tom; Yucel, Emre; Fonseca, Rafael
Abstract: Effects of disease progression on healthcare resource utilization (HRU) and costs among multiple myeloma (MM) patients with ≥1 line of therapy (LOT) and without receipt of stem cell transplant were estimated using large US claims database. Disease progression was defined as advancement to the next LOT, bone metastasis, hypercalcemia, soft tissue plasmacytoma, skeletal related events, acute kidney failure, or death within 12 months of LOT initiation. Annual HRU and costs in the first four LOTs were compared for patients with versus without progression using inverse probability of treatment weighting to adjust for differences between groups in baseline characteristics. In all LOTs, mean annual hospitalizations and healthcare costs were greater for patients with versus without progression. Total incremental annual costs among patients with versus without progression in 1LOT to 4LOT were 25, 920, 30, 632, 47, 320, and 19, 769, respectively. For MM patients receiving drug therapy, the economic burden of disease progression is substantial.